2015
DOI: 10.1242/jeb.130633
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical anaerobism in desert pupfish

Abstract: In order to estimate metabolic demands of desert pupfish for conservation purposes, we measured oxygen consumption in fish acclimated to the ecologically relevant temperatures of 28 or 33°C. For these experiments, we used fish derived from a refuge population of Devils Hole pupfish (Cyprinodon diabolis). Measurement of routine oxygen consumption (V O2,routine ) revealed some 33°C-acclimated fish (10% of 295 assayed fish) periodically exhibited periods of no measurable oxygen consumption despite available ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
(19 reference statements)
3
23
0
Order By: Relevance
“…The team then demonstrated that anaerobic metabolism did not contribute any substantial fraction of total energy expenditure in an ectotherm (ball python) [41]. The van Breukelen team has also recently demonstrated anaerobic metabolism in desert pupfish even in the absence of anoxia (paradoxical anaerobism) [42]. In 2013, our team demonstrated that anaerobic metabolism accounted for roughly 10% of total energy expenditure in laboratory mice (both C57BL/6J and FVB/NCrl strains) [43].…”
Section: Introductionmentioning
confidence: 99%
“…The team then demonstrated that anaerobic metabolism did not contribute any substantial fraction of total energy expenditure in an ectotherm (ball python) [41]. The van Breukelen team has also recently demonstrated anaerobic metabolism in desert pupfish even in the absence of anoxia (paradoxical anaerobism) [42]. In 2013, our team demonstrated that anaerobic metabolism accounted for roughly 10% of total energy expenditure in laboratory mice (both C57BL/6J and FVB/NCrl strains) [43].…”
Section: Introductionmentioning
confidence: 99%
“…Higher metabolism is strongly correlated with environmental temperature in fishes (Clarke & Johnston, ) and DHP persist in one of the hottest environments of any vertebrate species at 32°C year‐round in Devil's Hole (Stoike & Pister, ). Furthermore, DHP periodically goes into states of anaerobic metabolism for up to 2 hr, paradoxically reducing its metabolic efficiency even in the presence of oxygen and driving up its metabolic rate (Heuton, Ayala, Burg, & Dayton, ; Hillyard, Burg, McKenna, & Urbina, ). Second, higher metabolism is also correlated with smaller size (Gillooly, Brown, West, & Savage, ) and Devil's Hole pupfish are the smallest species of Cyprinodon (Stoike & Pister, ).…”
Section: Introductionmentioning
confidence: 99%
“…This point precedes blood circulation. Recently, our group reported unexpected oxygen consumption patterns in adult pupfish acclimated to 33°C (Heuton et al, 2015). Adult pupfish exhibit extended periods of little or no oxygen consumption that may be as long as 149 min continuous.…”
Section: Discussionmentioning
confidence: 97%